A clustered-based segmentation of beer consumers: from "beer lovers" to "beer to fuddle". Issue 6 (4th June 2018) - Calvo-Porral, Cristina; Orosa-González, Javier; Blazquez-Lozano, Felix
Abstract : Purpose: New trends are emerging in the brewery sector; but to date beer consumer segmentations are scarce. In this context, the present study addresses the following questions: "Are beer consumers monolithic or are there different segments in the beer market?; and "What are the main characteristics of the beer consumer segments?". The purpose of this paper is to examine the potential beer consumer segments and to profile them regarding their consumption behaviour. Design/methodology/approach: Data from a sample of 592 consumers were analysed through hierarchical cluster analysis; and the validity of the cluster solutions was then examined through a MANOVA analysis. Findings: A five-cluster solution emerged, revealing different beer consumption patterns and preferences. These segments are identified as "beer lovers", "circumspect seniors", "social drinkers", "homelike women" and "beer to fuddle consumers". Originality/value: The findings suggest that beer consumers cannot be seen as a homogenous consumer group; and managers and brewers could manage beer as five different products, instead of considering beer as a single item.